PROSES PEMBENTUKAN KOSAKATA BAHASA JEPANG (WAGO) - Lina Rosliana (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
Japanese (Nihongo), is a language spoken by over 130Â million people in Japan and in Japanese emigrant communities. Japanese vocabulary has been heavily influenced by loanwords from other languages. A vast number of words were borrowed from Chinese, or created from Chinese models, over a period of at least 1,500Â years. Since the late 19th century, Japanese has borrowed a considerable number of words from Indo-European languages, primarily English.